The pre-algebra course a bridge program for mathematically under-prepared college entrants - Mamhot, Millard R. (Silliman Journal, 2007)
One reality in our educational system is that a sizable number of our high school graduates are not prepared for college and a good portion of this are under-prepared to take regular college mathematics courses. A survey conducted in one of the state universities in Central Visayas, Philippines in school year 2004-2005 showed that about 90% of its college entrants have a hard time doing elementary operations on fractions, decimal, and percent. One resulting recommendation was that a bridge program be set up for these students. A subsequent study by Kilat (2006) noted five variables that most likely relate to students' grade in College Algebra: High School General Average (HSG), high School Mathematics Grade (HSM), Silliman University Admission and Placement Examination (SUAPE) Score, SUAPE Math component score (SM), and College Algebra Grade (CAG). Subjecting these variables to regression analysis reveals that CAG is strongly correlated with HSG and SM. The linear regression model with Durbin-Watson d statistic of 2.16 showed that CAG = 0.073SM - 6.23. With this equation, a desired CAG can be set to a certain value and the values of the other two variables may also be computed. A flowchart was drawn to aid the university admission office in identifying students who need to take the pre-algebra course. Three semesters after its completion, the percentage of those who obtained below average and failure significantly decreased from 39.77% to 29.67%. It is recommended that schools who wish to set up a bridge program for their incoming first year students adopt this method or a variation of this method according to the nature of their admission policy. If a school does not intend to put up a bridge program for their regular mathematics courses, it is suggested that students still be grouped according to their mathematical abilities in order to lighten the teacher's task of managing the classroom and diversifying one's approach to maximize effectiveness in transmitting mathematical knowledge to students.